Tüketici işlemi niteliğindeki taşınmaz satış sözleşmelerinde satıcının ayıptan sorumluluğu - Küçükbay, Esma (My University, 2021)
Türk Hukukunda taşınmaza yönelik sözleşmelerin tüketici hukuku kapsamına girmesi, 2003 yılında4077 sayılı Tüketicinin Korunması Hakkında Kanun’da 4822 sayılı Kanun’la yapılan değişikliklerlegerçekleşti. Söz konusu bu düşünce 2014 yılında yürürlüğe giren 6502 sayılı Tüketicinin KorunmasıHakkında Kanun’da (TKHK) da aynı şekilde devam etti. Kanun, taşınmaz ile konut ve tatil amaçlıtaşınmaz malı ifade ederek bir sınırlandırma getirse de konusu taşınmaz olan sözleşmelerin belirlenenbazı şartları sağlaması durumunda bu kanun kapsamında uygulama alanı bulacağını kabul etti. Hiçşüphe yok ki taşınmaza yönelik bu sözleşmelerin başında satış sözleşmeleri gelmektedir. Ayrıca kanunsözleşme türü açısından herhangi bir ayrım yapmadığı için konusu taşınmaz olan her türlü sözleşmeninde kanun kapsamına girmesini mümkün kıldı. Diğer taraftan TKHK önceki düzenlemelerden farklıolarak ön ödemeli konut satış sözleşmesini de kayıt altına alarak bir düzenleme getirdi ve bu sayedetamamlanmamış konutlar sebebiyle ortaya çıkan ihtilaflar bakımından da bu sözleşmelere yönelik bazıkanuni düzenlemeler sağlandı.Tüketicilere yönelik yapılan ayıplı ifa hallerinde tüketicinin başvurabileceği haklar ve bu haklara ilişkinaranan şartlar TKHK’da ayıptan sorumluluk hükümleri kapsamında ele alınmaktadır. Ancak söz konusuhallerde kanunda herhangi bir hüküm bulunmaması durumunda Türk Borçlar Kanunu’nun ilgilihükümleri uygulama alanı bulacaktır. Çalışmamızda konusu konut veya tatil amaçlı taşınmaz olan satışsözleşmelerinde TKHK hükümlerine göre ayıptan sorumluğun hüküm ve sonuçlarını değerlendirerek,bu sözleşmeler bakımından özellik arz eden durumları ortaya koymaya amaçladık.

The inclusion of contracts regarding real estate within the scope of consumer law in Turkish Law wasrealized with the amendments made in the Law No. 4822 in the Law No. 4077 on Consumer Protectionin 2003. This thought continued in the same way in the Law No. 6502 on the Protection of Consumers,which entered into force in 2014. Although the law introduces a limitation by expressing immovableproperty and immovable for residential and leisure purposes, it has accepted that if the contracts withthe subject of immovable meet certain conditions, they will find application within the scope of this law.There is no doubt that sales contracts are at the top of these contracts for real estate. In addition, sincethe law does not make any distinction in terms of the type of contract, it made it possible for any contractwith immovable subject to be covered by the law. On the other hand, unlike the previous regulations,the Law No. 6502 on the Protection of Consumers has also made a regulation by recording the prepaidhousing sales contract, and thus, some legal regulations were provided for these contracts in terms ofdisputes arising due to incomplete houses.In cases of defective performance against consumers, the rights that the consumer can apply and theconditions sought for these rights are dealt with under the provisions of liability for defects in the TKHK.However, in such cases, if there is no provision in the law, the relevant provisions of the Turkish Codeof Obligations will be applied. In our study, we aimed to reveal the peculiar situations in terms of thesecontracts by evaluating the terms and consequences of liability for defects in accordance with theprovisions of the Law No. 6502 on the Protection of Consumers in sales contracts, the subject of whichare residential or vacation properties.
Keywords: Ayıplıİfa Consumer Transaction; Civil law; Defective; Housing; Konut ve Tatil Amaçlı Taşınmaz Mal; Medeni hukuk; Satış Sözleşmesi; Tüketici İşlemi; Vacation Property